Pregnancy weight gain a balancing act: The experience and perspectives of women participating in a pilot randomised controlled trial. (March 2022) - Fealy, Shanna; Jones, Donovan; Davis, Deborah; Hazelton, Michael; Foureur, Maralyn; Attia, John; Hure, Alexis
Abstract: Background: Supporting women to achieve healthy gestational weight gain is a global health challenge. Inadequate and excessive gestational weight gains are associated with short and long-term adverse maternal and infant health outcomes. Qualitative studies suggest that symptoms of pregnancy, health professional attitudes, lack of guidance, personal knowledge and beliefs, lack of support, weight stigma, and lack of time and money, are barriers to achieving healthy weight gain. Less is known about women's perceptions and experience of gestational weight gain within normal body mass index categories with even less known about the experience of women motivated to participate in pregnancy weight management intervention trials. Aim: To describe the experience and perspectives of women participating in an Australian weight management pilot randomised controlled trial. Methods: Five women from regional New South Wales enrolled in the Eating 4 Two trial, participated in semi - structured interviews during the post-natal period. A qualitative descriptive methodology and inductive thematic analysis was applied. Findings: Two main themes emerged: 1) Addressing weight gain in pregnancy; and 2) Pregnancy weight the balancing act. Women identified weight gain as an important topic, the need for improvements within maternity services, responsive feedback and realistic support strategies. Women identified pregnancy symptoms, occurring during early and late pregnancy as barriers to achieving healthy weight gain. Conclusion: Further investigation into the effects of pregnancy symptoms on eating and physical activity patterns across pregnancy is warranted. Both qualitative and quantitative research is needed to monitor the translation of guideline recommendations into clinical practice.